(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To translate and evaluate the validity and reliability of a self-care assessment tool for patients with early-stage breast cancer. Methods: A methodological study was carried out with early stage breast cancer patients at K Hospital to translate and validate the Self-Care Behavior Scale. Content validity was assessed using the Item Content Validity Index (I-CVI) and the Scale Content Validity Index (S-CVI). Reliability was evaluated using Cronbach’s alpha coefficient, and construct validity was examined through Exploratory Factor Analysis (EFA). Results: Excellent content validity was demonstrated, with an I-CVI of 1.0 and an S-CVI of 1.0. A pilot study involving 30 patients indicated that the instrument was clear, understandable, and feasible for use. 50 patients in total participated in the validation phase. The instrument showed good consistency, with Cronbach’s alpha coefficients of 0.873 for the self-care scale and 0.838 for the quality-of-life scale. Exploratory Factor Analysis supported construct validity, with a Kaiser–Meyer–Olkin (KMO) value of 0.777 and a statistically significant Bartlett’s test of sphericity (p < 0.001). Conclusion: The Vietnamese version of the self-care assessment tool demonstrated validity and reliability, supporting its use in clinical practice and research among patients with early-stage breast cancer.